2018
DOI: 10.2337/db18-2347-pub
|View full text |Cite
|
Sign up to set email alerts
|

GDM—Impact of BMI in Maternal Bioquimical-Metabolic Variables and Its Association with Macrosomia

Abstract: Maternal Overweight/obesity increases risk of GDM and macrosomia Objectives: Compare pregestational BMI. Frequency of macrosomia. Correlationship between BMI first trimester fasting glycemia (1stTFG>92) fasting glycemia OGTT (FGOGTT), glycemia 120 minutes OGTT (2HPG), maternal weight gain during pregnancy (MWG) and macrosomía Research Design Methods: Analysis of 120 GDM medical records using ALAD diagnostic criteria. BMI categories were compared in Groups A ≥30 vs. ≤24.9 B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that maternal prepregnancy BMI was associated with the infant birth weight: women with low pre-pregnancy BMI had a higher risk of giving birth to LBW babies; on the other hand, high pre-pregnancy BMI was a risk factor for macrosomia [20,31,32] . The Zhuang women in our study had lower pre-pregnancy BMI (5.91% overweight or obesity) than women in other cohort study (9% overweight or obesity in Shanghai and 11.72% in Ma'anshan) [26,33] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that maternal prepregnancy BMI was associated with the infant birth weight: women with low pre-pregnancy BMI had a higher risk of giving birth to LBW babies; on the other hand, high pre-pregnancy BMI was a risk factor for macrosomia [20,31,32] . The Zhuang women in our study had lower pre-pregnancy BMI (5.91% overweight or obesity) than women in other cohort study (9% overweight or obesity in Shanghai and 11.72% in Ma'anshan) [26,33] .…”
Section: Discussionmentioning
confidence: 99%